UJI POTENSI PENURUNAN KADAR KHOLESTEROL MENCIT (Mus musculus) DARI INFUSA DAUN KERSEN (Muntingia calabura L.) SEGAR DAN SIMPLISIA - suharti; Risa Kota Putra; Ibnu Sobana (Jurnal Buana Farma, 2024)
Hyperlipidemia is a condition where an increase in one or all of the lipids in the bloodstream (plasma) is an important risk factor for cardiovascular disease. Cherry plant (Muntingia calabura L.) contains chemicals flavonoids, tannins, ascorbic acid and saponins. Traditionally it is believed to help treat various diseases, such as protecting heart muscle function, anti-diabetic, anti-hypertensive, anti-inflammatory, antiseptic and anti-tumor. Potential to reduce blood cholesterol levels from the cherry plant is due to the presence of flavonoid compounds and ascorbic acid as active antioxidants that prevent LDL oxidation in the blood. This study aims to determine the potential for reducing cholesterol levels from cherry leaves in the form of fresh infusion preparations and simplicia infusion preparations, preparations given orally to male white mice (Mus musculus) whose blood cholesterol levels were previously induced by quail egg yolk feed at a dose per mouse. 73 mg (equivalent to 0.3 ml). Every day for 15 days, then the blood cholesterol level is measured using the Easy Touch GCU device. As a comparison in this study, simvastatin tablets were used. The test results for the potential to reduce blood cholesterol levels of fresh cherry leaves and their simplicia show that the infusion of fresh leaves has a stronger effect on lowering cholesterol levels than the simplicia (dry), it can be concluded that blood cholesterol levels can be reduced in the infusion of fresh cherry leaves (Average decrease cholesterol 18 mg/dl) is stronger than the simplicia (dry) infusion (average reduction in cholesterol levels 17 mg/dl).